Mark-recapture models identify imminent extinction of Yaqui catfish Ictalurus pricei in the United States. (May 2017) - Stewart, David R.; Butler, Matthew J.; Harris, Grant; Radke, William R.
Abstract: Data describing population abundance, survival, and recruitment informs species conservation status and conservation actions. Acquiring these data remains challenging for rare and endangered species, especially freshwater fish, with ~ 37% threatened or extinct. The absence of data risks inaction, ineptness and ignorance that can contaminate conservation decisions to the species detriment. The solution is obvious: ensure credible data underpin species conservation. We focus on Yaqui catfish ( Ictalurus pricei ), an endangered, freshwater endemic to the Sonoran desert (Arizona, US and Sonora, Mexico). Our method incorporates mark-recapture data, coupled with hierarchical Bayesian state-space formulations of the Cormack-Jolly Seber models and Jolly-Seber models, to quantify species growth, survival probability, recruitment probability, abundance and trends for the US population. Yaqui catfish growth matched other Ictalurid species. Population recruitment is essentially zero (< 0.01%) and annual survival high (> 70–75%). Overall, the US Yaqui catfish population declined by 15% per year (λ = 0.85). Remaining catfish represent remnants of stocked progeny from the 1990s (age of 19–21 years), with US extinction predicted by 2018. A pulse of conservation activity followed by 20 years of unsuccessful management resulted in the US population collapsing while habitat degradation and introgression from non-native fish threaten most populations in Mexico. Now approaching global extinction, saving Yaqui catfish requires collaboration between Mexican and US biologists to establish species status in Mexico, hatchery cultivation, habitat protection, habitat restoration and appropriate monitoring. Work herein springboards recent conservation efforts to secure this species. Highlights: Yaqui catfish Ictalurus pricei growth matched other Ictalurus species. Population recruitment is essentially zero (< 0.01%) and annual survival high (> 70–75%). The United States Yaqui catfish population declined by 15% per year (λ = 0.85) from 2000 to 2015. Remaining individuals represent remnants of stocked progeny from the 1990s (age of 19–21 yrs). Extinction in the United States is predicted by 2018.